Foundations of Java for ABAP Programmers - Rooney, Alistair; SpringerLink (Online service) (Berkeley, CA : Apress, 2006)
The only beginning book of its kind, this book will teach you SAP/ABAP developers the skills you need for Java 5 programming. The book emphasizes the fundamentals of core Java SE 5 and Java EE 5, to get you up to speed with these technologies. You'll learn about the most important enterprise Java API found in the new Java EE 5 platform, which you can immediately use and integrate. Furthermore, the book elaborates on connecting to a database, SAP Java Connector, servlets, Java Server Pages, Enterprise JavaBeans, and Java Messaging.
Introducing Java -- Your First Java Program -- Object Orientation in a Nutshell -- The Primitive Data Types -- Comments -- Naming Standards and Conventions -- The Java Operators -- Strings with Java -- Control Flow -- Jump Statements -- Arrays and Collections in Java -- Object Orientation in Java -- More OO in Java$1 (BInterfaces and Abstract Classes -- Inner, Nested, and Anonymous Classes -- Errors and Exceptions -- Threads, Daemons, and Garbage Collection -- Basic Swing Using Default Layouts -- Event Handling -- Layout Managers and Other Components -- Enterprise Java -- JDBC Technology -- The Java Connector (JCo) -- Servlets -- JavaServer Pages (JSP) -- Extensible Markup Language (XML) -- Java Messaging Services -- Enterprise JavaBeans 3.0.s
Keywords: Computer science; Software engineering; Computer Science; Software Engineering/Programming and Operating Systems; Electronic books